2021
DOI: 10.3390/biomedicines9101342
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses against SARS-CoV-2—Questions and Experiences

Abstract: Understanding immune reactivity against SARS-CoV-2 is essential for coping with the COVID-19 pandemic. Herein, we discuss experiences and open questions about the complex immune responses to SARS-CoV-2. Some people react excellently without experiencing any clinical symptoms, they do not get sick, and they do not pass the virus on to anyone else (“sterilizing” immunity). Others produce antibodies and do not get COVID-19 but transmit the virus to others (“protective” immunity). Some people get sick but recover.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 182 publications
(262 reference statements)
0
14
0
Order By: Relevance
“…Vaccination against SARS-CoV-2 is a leading strategy to change the course of the COVID-19 pandemic worldwide, reducing the risk of infection, that of severe complications and the long-term effects in the case of a breakthrough infection ( 8 , 9 , 21 ). Moreover, vaccines have shown to increase immunogenicity, antibody titres, and reactogenicity in individuals with past infection compared with naive patients ( 22 ). Vaccine hesitancy of previously infected patients and long-haulers might be due to the belief that, having developed a dysregulated response to natural infection, that may be exacerbated by vaccination, and also to the perception that protection is acquired with previous infection, as observed in our cohort ( 11 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccination against SARS-CoV-2 is a leading strategy to change the course of the COVID-19 pandemic worldwide, reducing the risk of infection, that of severe complications and the long-term effects in the case of a breakthrough infection ( 8 , 9 , 21 ). Moreover, vaccines have shown to increase immunogenicity, antibody titres, and reactogenicity in individuals with past infection compared with naive patients ( 22 ). Vaccine hesitancy of previously infected patients and long-haulers might be due to the belief that, having developed a dysregulated response to natural infection, that may be exacerbated by vaccination, and also to the perception that protection is acquired with previous infection, as observed in our cohort ( 11 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the presence and persistence of RBD IgG stimulated by the vaccine in patients with hybrid immunity were not associated with post-COVID-19 compared with patients with natural infection. The immune response induced by vaccines is a highly targeted response to the Spike protein of the SARS-CoV-2 virus and may help the immune system to tackle the possible viral reservoir, reducing the chance of non-specific immune reactions and resetting the immune response ( 22 , 26 , 28 , 29 ). In contrast, the response triggered by natural infection is broader and may stimulate an excessive or dysregulated allo- and autoimmune response and uncontrolled inflammatory activity ( 22 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that a longer interval between two doses of a vaccine promotes a better immune response, as shown with the Pfizer/BioNTech vaccine. Data suggest that twodose vaccination may induce a better immune response to SARS-CoV-2 than homologous single-dose vaccination [40].…”
Section: Discussionmentioning
confidence: 99%
“…In the end, Transmembrane protease serine 2 (TMPRSS2) leads to continuous virus entry into cells, but its expression is upregulated by androgens [ 26 , 27 ]. Different immune responses, the RAAS system, ACE2, and TMPRSS2 role, and hormonal status are biological sex-related differences that count markedly towards the different COVID-19 progression among the sexes [ 28 , 29 , 30 , 31 , 32 ]. Gender, profoundly understudied, counts significantly in this context [ 33 ].…”
Section: Introductionmentioning
confidence: 99%